2011
DOI: 10.1590/s0103-50532011000600011
|View full text |Cite
|
Sign up to set email alerts
|

A green method for determination of acid number of biodiesel

Abstract: Neste trabalho é proposto um método simples e verde para a determinação do índice de acidez do biodiesel. A amostra é dissolvida em solução 1:1 v/v etanol:água, evitando a mistura tolueno:isopropanol:água (1:0,95:0,5 v/v/v) usada nas normas atuais. A titulação é realizada com uma solução aquosa de NaOH 0,02 mol L -1 . O método foi comparado com o da ABNT NBR 14448, que é similar ao do ASTM D 664 e do EN 14104. A comparação estatística utilizando o teste pareado t de student e o teste F de Snedecor mostrou que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…Another challenge for using organic solvents is that toxic chemical waste is generated when analyzing the TAN value by standard methods due to the titration solvent. Therefore, many researchers have indicated that current standard methods are labor-intensive, expensive, error-prone, and harmful to the environment [14,16,17,23].…”
Section: Today Various Standard Methods (Summarized Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge for using organic solvents is that toxic chemical waste is generated when analyzing the TAN value by standard methods due to the titration solvent. Therefore, many researchers have indicated that current standard methods are labor-intensive, expensive, error-prone, and harmful to the environment [14,16,17,23].…”
Section: Today Various Standard Methods (Summarized Inmentioning
confidence: 99%
“…TAN is the amount of potassium hydroxide (KOH, in milligram) required to titrate one gram of a sample. The TAN analysis was originally developed for measuring the acidity of petroleum products but has been applied more recently to measure the acidity of biodiesel [14][15][16][17][18][19][20][21][22][23], biodiesel blends [15,16,20], vegetable oils [18,24], lubricating oils [25], heavy oil [26], bitumens [26], fats [24], and bio-oil [4,9,12,27].…”
Section: Regardless Of Differing Characteristics Between Various Bio-mentioning
confidence: 99%
“…Compared to previously proposed procedures [13,14,18,23,24] for acid number determination ( Table 2) and official procedures [11,12], the present proposal has as the main advantage the mechanization of the FFA microextraction in a closed system, which improves the repeatability. Moreover, manual titrations are prone to errors caused by disability of the analyst to detect the end point, besides being time consuming.…”
Section: Analytical Features and Applicationmentioning
confidence: 90%
“…However, only few more environmental friendly analytical procedures have been proposed in the literature. In contrast to the use of toxic organic solvents to dissolve biodiesel, such as a mixture of toluene, isopropanol, and water in the volumetric ratio of 100:99:1 (ASTM D664) or 1:1 v/v diethyl ether and ethanol (EN 14104), a 1:1 v/v ethanol:water solution was proposed for both potentiometric [13] and visual [14] titrations. Biodiesel diluted in ethanol was used in a voltammetric procedure for acid number determination using a glassy carbon electrode [15].…”
Section: Introductionmentioning
confidence: 99%
“…Boron-doped diamond 119 is a relatively recently developed electrode-material characterised by low background currents (thus yielding better detection limits) and being less susceptible to adsorption effects, which is advantageous for analysis of samples with high contents of organic species, such as biodiesel. 122 The main limitation of the proposed methods is the monoelement character, with the exception of certain amperometric procedures and contactless conductometric detection coupled with capillary electrophoresis. The standard additions method is also a useful alternative.…”
Section: Electrochemical Detectionmentioning
confidence: 99%